99mTc-MIBI Lung Scintigraphy in the Assessment of Pulmonary Involvement in Interstitial Lung Disease and Its Comparison With Pulmonary Function Tests and High-Resolution Computed Tomography: A Preliminary Study. Issue 47 (November 2015) - Bahtouee, Mehrzad; Saberifard, Jamshid; Javadi, Hamid; Nabipour, Iraj; Raeisi, Alireza; Assadi, Majid; Eftekhari, Mohammad
Abstract : Abstract: The differentiation of active inflammatory processes from an inactive form of the disease is of great value in the management of interstitial lung disease (ILD). The aim of this investigation was to assess the efficacy of 99mTc-methoxy-isobutyl-isonitrile (99mTc-MIBI) scans in distinguishing the severity of the disease compared to radiological and clinical parameters. In total, 19 known cases of ILD were included in this study and were followed up for 1 year. Five patients without lung disease were considered as the control group. The patients underwent pulmonary function tests (PFTs) and high-resolution computed tomography scans, followed by 99mTc-MIBI scanning. The 99mTc-MIBI scans were analyzed either qualitatively (subjectively) or semiquantitatively. All 19 ILD patients demonstrated a strong increase in 99mTc-MIBI uptake in the lungs compared to the control group. The 99mTc-MIBI scan scores were higher in the patient group in both the early phase (0.24[0.19–0.31] vs 0.11[0.10–0.15], P  < 0.05) and the delayed phase (0.15[0.09–0.27] vs 0.04[0.01–0.09], P  < 0.05) compared with the control group. A positive correlation was detected between the 99mTc-MIBI scan and the high-resolution computed tomography (HRCT) scores (Spearman's correlation coefficient = 0.65, P  < 0.02) in the early phase but not in the delayed phase in patients ( P  > 0.14). The 99mTc-MIBI scan scores were not significantly correlated with the PFT findings ( P  > 0.05). In total, 5 patients died and 14 patients were still alive over the 1-year follow-up period. There was also a significant difference between the uptake intensity of 99mTc-MIBI and the outcome in the early phase (dead: 0.32[0.29–0.43] vs alive: 0.21[0.18–0.24], P  < 0.05) and delayed phase (dead: 0.27[0.22–0.28] vs alive: 0.10[0.07–0.19], P  < 0.05). The washout rate was ∼40 min starting from 20 min up to 60 min and this rate was significantly different in our 2 study groups (ILD: 46.61[15.61–50.39] vs NL: 70.91[27.09–116.36], P  = 0.04). The present study demonstrated that 99mTc-MIBI lung scans might distinguish the severity of pulmonary involvement in early views, which were well correlated with HRCT findings. These results also revealed that 99mTc-MIBI lung scans might be used as a complement to other diagnostic and clinical examinations in terms of functional information in ILD; however, further investigations are strongly required.